A randomized pilot trial assessing the reduction of gout episodes in hyperuricemic patients by oral administration of Ligilactobacillus salivarius CECT 30632, a strain with the ability to degrade purines - Rodríguez, Juan M.; Garranzo, Marco; Segura, José; Orgaz, Belén; Arroyo, Rebeca; Alba, Claudio; Beltrán, David; Fernández, Leónides (Frontiers in Microbiology, 2023)
Introduction Hyperuricemia and gout are receiving an increasing scientific and medical attention because of their relatively high prevalence and their association with relevant co-morbidities. Recently, it has been suggested that gout patients have an altered gut microbiota. The first objective of this study was to investigate the potential of some Ligilactobacillus salivarius strains to metabolize purine-related metabolites. The second objective was to evaluate the effect of administering a selected potential probiotic strain in individuals with a history of hyperuricemia. Methods Inosine, guanosine, hypoxanthine, guanine, xanthine, and uric acid were identified and quantified by high-performance liquid chromatography analysis. The uptake and biotransformation of these compounds by a selection of L. salivarius strains were assessed using bacterial whole cells and cell-free extracts, respectively. The efficacy of L. salivarius CECT 30632 to prevent gout was assessed in a pilot randomized controlled clinical trial involving 30 patients with hyperuricemia and a history of recurrent gout episodes. Half of the patients consumed L. salivarius CECT 30632 (9 log10 CFU/day; probiotic group; n = 15) for 6 months while the remaining patients consumed allopurinol (100–300 mg/daily; control group; n = 15) for the same period. The clinical evolution and medical treatment received by the participants were followed, as well as the changes in several blood biochemical parameters. Results L. salivarius CECT 30632 was the most efficient strain for inosine (100%), guanosine (100%) and uric acid (50%) conversion and, therefore, it was selected for the pilot clinical trial. In comparison with the control group, administration of L. salivarius CECT 30632 resulted in a significant reduction in the number of gout episodes and in the use of gout-related drugs as well as an improvement in some blood parameters related to oxidative stress, liver damage or metabolic syndrome. Conclusion Regular administration of L. salivarius CECT 30632 reduced serum urate levels, the number of gout episodes and the pharmacological therapy required to control both hyperuricemia and gout episodes in individuals with a history of hyperuricemia and suffering from repeated episodes of gout.